2021
DOI: 10.1093/jac/dkab223
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of nikkomycin Z in murine CNS coccidioidomycosis: modelling sustained-release dosing

Abstract: Objectives Meningitis is the most feared coccidioidomycosis complication. Nikkomycin Z (nikZ) is a chitin synthase inhibitor. A concern is short half-life, necessitating multiple dose/day regimens. We simulated extended release, providing nikZ in drinking water. Extended release would enhance convenience, and adherence, for patients. Methods Coccidioides posadasii was injected intracerebrally into mice. Twelve day treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Taken together, the findings might suggest NIKZ may be particularly useful in renal fungal infections. Studies in other models have also indicated NIKZ efficacy in other organs, including lung and brain 5,6,28,36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the findings might suggest NIKZ may be particularly useful in renal fungal infections. Studies in other models have also indicated NIKZ efficacy in other organs, including lung and brain 5,6,28,36 …”
Section: Discussionmentioning
confidence: 99%
“…Studies in other models have also indicated NIKZ efficacy in other organs, including lung and brain. 5,6,28,36 A second possible factor relates to candidal physiology and the mechanism of action of NIKZ. Mycelial formation is one virulence factor for C. albicans, and occurs in tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Promising results were observed in a phase II study of dogs with CM. However, well-designed clinical trials are not available to confirm its effectiveness and safety profile in patients with CM [ 72 , 73 , 74 , 75 ].…”
Section: Coccidioidomycosismentioning
confidence: 99%
“…The few existing murine studies on the dissemination of coccidioidomycosis have focused on the spleen, lungs, liver, kidneys, and brain. These include studies of the immune response to systemic C. immitis infection of the lungs, spleen, and liver [67], C. immitis tissue invasiveness in lungs, liver, spleen, and kidneys [68] as well as the drug efficacy against disseminated coccidioidomycosis in lungs, spleen, liver and CNS [69][70][71]. To our knowledge, no investigation using rodent animal models has been performed to study the dissemination of coccidioidomycosis to bones and joints.…”
Section: Animal Studiesmentioning
confidence: 99%